La psicoanalisi ontologica ovvero «Che cosa vuoi essere da grande?» - Ogden, Thomas H. (B@belonline, 2021)
The Author discusses the differences between what he calls epistemological psychoanalysis (having to do with knowing and understanding), of which Freud and Klein are the main exponents, and ontological psychoanalysis (having to do with being and becoming), of which Winnicott and Bion are the main proponents. Winnicott shifts the focus of psychoanalysis from the symbolic meaning of play to the experience of playing; Bion shifts the focus from the symbolic meaning of dreams to the experience of dreaming in all its forms. Epistemological psychoanalysis is primarily concerned with working toward an understanding of unconscious meaning; in contrast, the goal of ontological psychoanalysis is to allow the patient the experience of creatively discovering meaning for him or herself and, in that state of being, becoming more fully vital.